Highly Mg‐doped GaN dots and films grown by VLS transport at low temperature. Issue 4 (26th September 2016) - Jaud, Alexandre; Auvray, Laurent; Kahouli, Abdelkarim; Abi‐Tannous, Tony; Cauwet, François; Ferro, Gabriel; Brylinski, Christian
Abstract : In this study, a new approach toward localized p‐type doping of GaN was explored by implementing vapor–liquid–solid (VLS) transport for both reducing the growth temperature and reaching very high Mg incorporation levels. The starting seeds are GaN(0001) epilayers grown on Si(111). The growth cycle includes three steps. At first, Ga is deposited by MOCVD onto the GaN surface, resulting in a network of Ga droplets with sub‐micrometer diameters. Then, Mg is incorporated into the droplets, from the gas phase, using (MeCP)2 Mg precursor. Finally, droplets are nitridated at 600–700 °C in flowing NH3 . Performing one complete growth cycle leads to a network of well‐separated dots and/or ring‐shaped GaN features. It is demonstrated that the Mg content in the droplets drastically influences the GaN growth mode. Increasing Mg incorporation promotes growth at the liquid/solid interface versus growth at the triple line. To improve the seed coverage, several successive cycles have been performed leading to GaN films with thickness up to ∼250 nm. SIMS analyses demonstrate the very high incorporation of Mg in the VLS‐grown material, with concentrations from 3 × 10 19 to 8 × 10 21  cm −3 . Nevertheless, pronounced O incorporation (a few 10 20  cm −3 ) is also found.